Molecular, Immunological, and Clinical Features Associated With Lymphoid Neogenesis in Muscle Invasive Bladder Cancer - Pagliarulo, Fabio; Cheng, Phil F.; Brugger, Laurin; van Dijk, Nick; van den Heijden, Michiel; Levesque, Mitchell P.; Silina, Karina; van den Broek, Maries (Frontiers in Immunology, 2022)
Lymphoid neogenesis gives rise to tertiary lymphoid structures (TLS) in the periphery of multiple cancer types including muscle invasive bladder cancer (MIBC) where it has positive prognostic and predictive associations. Here we explored molecular, clinical, and histological data of The Cancer Genome Atlas, as well as the IMvigor210 dataset to study factors associated with TLS development and function in the tumor microenvironment (TME) of MIBC. We also analyzed tumor immune composition including TLS in an independent, retrospective MIBC cohort. We found that combination of TLS density and tumor mutational burden provides a novel independent prognostic biomarker in MIBC. Gene expression profiles obtained from intratumoral regions that rarely contain TLS in MIBC showed poor correlation with the prognostic TLS density measured also in tumor periphery. Tumors with high TLS density showed increased gene signatures as well as infiltration of activated lymphocytes. Intratumoral B cell and CD8+ T cell co-infiltration was frequent in TLS-high samples, and such regions harbored the highest proportion of PD-1+TCF1+ progenitor-like T cells, naïve T cells and activated B cells when compared to regions predominantly infiltrated by either B cells or CD8+ T cells alone. We found four TLS maturation subtypes; however, differences in TLS composition appeared to be dictated by the TME and not by the TLS maturation status. Finally, we identified one downregulated and three upregulated non-immune cell-related genes in TME with high TLS density, which may represent candidates for tumor-intrinsic regulation of lymphoid neogenesis. Our study provides novel insights into TLS-associated gene expression and immune contexture of MIBC and indicates towards the relevance of B cell and CD8+ T cell interactions in anti-tumor immunity within and outside TLS.